A influência de diferentes processamentos nas características finais de uma emulsão fotoprotetora - Santos, Yasmin Rosa [UNIFESP] (2020)
Emulsion is a system formed by the dispersion of two immiscible phases, where the ingredients that compose it are subjected to certain emulsification process to obtain it. Among the various processing techniques, high energy processes are indicated for reducing the particle size of the emulsion, an alternative to avoid phase separation during the period of shelf-life because the emulsion is a thermodynamically unstable system. To investigate the impact of processing in a photoprotective emulsion, the present work evaluated two distinct high energy methods, capable of decreasing the size of particles by high energy, the High-Pressure Method (MAP), performed in the high homogenizer pressure; and the High-Speed ​​Method (MAV), performed with high-cut agitation equipment. The MAP and MAV tests were planned using a DoE (Design of Experiments) of 3² for each method, where in the first MAP the variables used were the pressure (5000, 10000 and 15000 psi) and the number of sample passes through the equipment ( 1, 3 or 5 passages); and in the MAV DoE, the factors of agitation speed (5000, 10,000 and 15,000 rpm) and processing time (3, 7 and 15 minutes) were varied. The 22 formulations of DoEs were characterized in Part I (organoleptic characteristics, resistance to centrifugation, pH, particle size by two different techniques [Static Light Scattering and Dynamic Light Scattering], Zeta potential, rheological behavior and SPF in vitro) over time (T0) and after 3 freeze-thaw cycles (T6). In Part II, five samples of each method were selected to monitor the performance and physico-chemical characteristics for 90 days under different storage conditions. The results of Part I indicate that the MAV and MAP samples showed significant differences (p <0.05) in most evaluations, for example, the formulation with emulsification process of 15000 rpm for 15 minutes of agitation of the MAV reached SPF 42, starting from a primary emulsion of SPF 30. MAP showed a higher reduction in particle size, but there was phase separation in the emulsions where the pressures of 10,000 and 15,000 psi were applied. In Part II, many attributes evaluated showed reproducibility about the results of Part I in the initial time. However, the conditions and the storage time caused significant changes in some analyzes, like SPF, where the results showed a significant increase.With that, it was concluded that the different forms of processing can influence the physical-chemical and performance characteristics of an emulsion. In the case of the studied primary emulsion, the MAV presented more satisfactory results, mainly in the tests of high agitation time and speed.